Pore-forming and enzymatic activities of Bordetella pertussis adenylate cyclase toxin synergize in promoting lysis of monocytes - Basler, Marek; Masin, Jiri; Osicka, Radim; Sebo, Peter (Infection and immunity, 2006)
Bordetella adenylate cyclase (AC) toxin-hemolysin (CyaA) targets myeloid phagocytes expressing the alphaMbeta2 integrin (CD11b/CD18) and delivers into their cytosol an AC enzyme that converts ATP into cyclic AMP (cAMP). In parallel, CyaA acts as a hemolysin, forming small membrane pores. Using specific mutations, we dissected the contributions of the two activities to cytolytic potency of CyaA on J774A.1 murine monocytes. The capacity of AC to penetrate cells and deplete cytosolic ATP was essential for promoting lysis and the enzymatically inactive but fully hemolytic CyaA-AC- toxoid exhibited a 15-fold-lower cytolytic capacity on J774A.1 cells than intact CyaA. Moreover, a two- or fourfold drop of specific hemolytic activity of the CyaA-E570Q and CyaA-E581P mutants was overpowered by an intact capacity to dissipate cytosolic ATP into cAMP, allowing the less hemolytic proteins to promote lysis of J774A.1 cells as efficiently as intact CyaA. However, an increased hemolytic activity, due to lysine substitutions of glutamates 509, 516, and 581 in the pore-forming domain, conferred on AC- toxoids a correspondingly enhanced cytolytic potency. Moreover, a threefold increase in hemolytic activity could override a fourfold drop in capacity to convert cellular ATP to cAMP, conferring on the CyaA-E581K construct an overall twofold increased cytolytic potency. Hence, although appearing auxiliary in cytolytic action of the toxin on nucleated cells, the pore-forming activity can synergize with ATP-depleting activity of the cell-invasive AC enzyme and complement its action toward maximal cytotoxicity.
Keywords: CD11b Antigen; Erythrocytes; buněčná smrt; Cell Line; Cyclic AMP; CD18 Antigens; Cricetulus; monocyty; CHO Cells; Cricetinae; křečci praví; erytrocyty; zvířata; Animals; Adenylate Cyclase Toxin; Monocytes; Mice; Cell Death; antigeny CD18; CHO buňky; permeabilita buněčné membrány; myši; cytotoxicita imunologická; Bordetella pertussis; antigeny CD11b; buněčné linie; adenylátcyklasový toxin; Cell Membrane Permeability; Sheep; adenosintrifosfát; Cytotoxicity, Immunologic; ovce; AMP cyklický; Adenosine Triphosphate